Triethylammonium hydrogen sulfate ionic liquid as a low-cost solvent: A short review of synthesis, analysis and applications - Shikh Mohd Shahrul Nizan Shikh Zahari; Azman H.; Karim L. (EDP Sciences, 2024)
Indexed by Scopus